Communicating Sustainable Brand Equity in a High Carbon Footprint and High-Risk Sector: Comparing Malaysia and Indonesia Oil and Gas Industry - Md Nordin, Shahrina; Mokhtar, Nor Izzah; Priyadi, Unggul; Tarjo, Tarjo; Wan Ahmad, Wan Fatimah; Ahmad Rizal, Ammar Redza (2023)
The oil and gas industry is classified as a high carbon footprint and high-risk sector from the sustainable development perspective. Its operational activities risk potential threats to the environment and the local community. Globally, there are multiple cases of local community discontent towards oil and gas operations in their area. Consequently, the oil and gas industry shifted into corporate social responsibility (CSR) activities to indicate their dedication to sustainability. Studies have been conducted to investigate the impact of CSR activities on the oil industry. However, there is still limited research looking into sustainable brand positioning, which might be affected by the execution of multiple CSR programs by the industry. Looking into the oil and gas industry in Malaysia and Indonesia, this study compared the industry’s sustainable brand positioning amongst the local community. By adopting Aakker’s brand equity model, this study investigated the effect of sustainable brand awareness, the perceived quality of sustainable initiatives, brand association, and brand loyalty on sustainable initiatives towards sustainable brand equity. There are 448 respondents involved from both Malaysia and Indonesia. Using PLS-MGA, this study identified that brand loyalty on sustainable initiatives and brand association are significant predictors of sustainable brand equity. Findings from this study also indicate that no group (i.e., Indonesia and Malaysia) is significantly larger than one other in the path coefficient score. However, using an independent sample t-test, the study indicates that the oil and gas industry has better sustainable brand positioning amongst Malaysia’s local community than Indonesia.